2017
DOI: 10.1186/s12864-017-3650-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative and functional genomics of the Lactococcus lactis taxon; insights into evolution and niche adaptation

Abstract: Background Lactococcus lactis is among the most widely studied lactic acid bacterial species due to its long history of safe use and economic importance to the dairy industry, where it is exploited as a starter culture in cheese production.ResultsIn the current study, we report on the complete sequencing of 16 L. lactis subsp. lactis and L. lactis subsp. cremoris genomes. The chromosomal features of these 16 L. lactis strains in conjunction with 14 completely sequenced, publicly available lactococcal chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
83
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 71 publications
4
83
2
1
Order By: Relevance
“…cremoris strains are adapted to a milk environment and are used for industrial fermentations. It has been suggested that the high number of pseudogenes could indicate ongoing specialization of the strains to their current niche, with constant degeneration of dispensable genes and their encoded functions (5,7). Genome decay was reproduced in an experimental evolution study through cultivation of the plant isolate Lactococcus lactis subsp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…cremoris strains are adapted to a milk environment and are used for industrial fermentations. It has been suggested that the high number of pseudogenes could indicate ongoing specialization of the strains to their current niche, with constant degeneration of dispensable genes and their encoded functions (5,7). Genome decay was reproduced in an experimental evolution study through cultivation of the plant isolate Lactococcus lactis subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Various L. lactis strains can be found in many different environments, such as plants, milk, animals, and related niches (1,2). Although a number of L. lactis strains have been "domesticated" and cultivated in milk for many years, thorough analyses of L. lactis genomes reveals the presence of multiple silent gene clusters and pseudogenes with predicted functions in plant sugar utilization as remnants of their plant niche-related history (2)(3)(4)(5)(6)(7). Point mutations and genome rearrangements occasionally lead to activation of silent genes and gene clusters, sometimes even granting them new functions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This status quo may limit the excavation of other functions of L. mucosae, which requires more strains. With the rapid development of bioinformatics, comparative genomics provides a novel way to effectively assess the genetic diversity of bacteria [14], which could explore the origin of the strain and determine the genetic distribution of a particular species [15]. In 2017, Valeriano et al [6] firstly analyzed the potential specific genes and intestinal adaptability of L. mucosae LM1 through genome comparison, such as the average nucleotide identity (ANI) analysis with other species and collinearity analysis within species; unfortunately, the number of strains involved was limited.…”
Section: Introductionmentioning
confidence: 99%
“…The first step in the use of casein by lactic acid bacteria is performed by CEP. Five different types of these enzymes (PrtP endoprotease, 2 general PepN and PepC aminopeptidases, PepO1 endopeptidase and Opp oligopeptide transport system) were cloned and characterized, including PrtP from L. lactis, whose gene (prtP) can be found either on plasmidic or chromosomic DNA, while the CEPs of lactobacilli are coded by genes on chromosomic DNA (Holck and Naes, 1992;Guédon et al, 2001;Kelleher et al, 2017).…”
Section: Proteolysis Activitymentioning
confidence: 99%